2016
DOI: 10.1007/s12199-016-0538-y
|View full text |Cite
|
Sign up to set email alerts
|

Short stature is an inflammatory disadvantage among middle-aged Japanese men

Abstract: Independent of classical cardiovascular risk factors, height was found to be inversely associated with high WBC count, especially for those with a BMI ≥ 23 kg/m. Compared to high stature, short stature appears to convey an inflammatory disadvantage among Japanese men, especially those with a BMI ≥ 23 kg/m.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 21 publications
3
30
0
Order By: Relevance
“…In the present study, to evaluate the influence of height on progressive vascular remodeling, further analyses showed no-significant association between height and CIMT for subjects with both high and low hemoglobin; fully-adjusted standardized parameter estimates (β) and p-values were β = −0.001, p = 0.992 for subjects with high hemoglobin and β = 0.11, p = 0.290 for subjects with low hemoglobin. Since our present study population comprised individuals within the normal BMI range (18.5-24.9 kg/m 2 ) our present results are compatible with those of previous studies we conducted [2,5]. However, atherosclerosis (increased CIMT) is only one aspect of vascular repair (aggressive endothelial repair).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…In the present study, to evaluate the influence of height on progressive vascular remodeling, further analyses showed no-significant association between height and CIMT for subjects with both high and low hemoglobin; fully-adjusted standardized parameter estimates (β) and p-values were β = −0.001, p = 0.992 for subjects with high hemoglobin and β = 0.11, p = 0.290 for subjects with low hemoglobin. Since our present study population comprised individuals within the normal BMI range (18.5-24.9 kg/m 2 ) our present results are compatible with those of previous studies we conducted [2,5]. However, atherosclerosis (increased CIMT) is only one aspect of vascular repair (aggressive endothelial repair).…”
Section: Discussionsupporting
confidence: 89%
“…In a previous study, we reported an inverse association between height and high white blood cell count in those with a BMI ≥ 23kg/m 2 but not with a BMI < 23 kg/m 2 [5]. Since a high white blood cell count, which indicates elevated inflammatory activity, is significantly positively associated with atherosclerosis [4], height may be inversely associated with this disease.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations